Optical Coherence Tomography (OCT) Findings in Post-COVID-19 Healthcare Workers - Sanela Sanja Burgić; Mirko Resan; Milka Mavija; Saša Smoljanović Skočić; Sanja Grgić; Daliborka Tadić; Bojan Pajic (Journal of Imaging, 2025)
Recent evidence suggests that SARS-CoV-2 may induce subtle anatomical changes in the retina, detectable through advanced imaging techniques. This retrospective case–control study utilized optical coherence tomography (OCT) to assess medium-term retinal alterations in 55 healthcare workers, including 25 individuals with PCR-confirmed COVID-19 and 30 non-COVID-19 controls, all of whom had worked in COVID-19 clinical settings. Comprehensive ophthalmological examinations, including OCT imaging, were conducted six months after infection. The analysis considered demographic variables, comorbidities, COVID-19 severity, risk factors, and treatments received. Central macular thickness (CMT) was significantly increased in the post-COVID-19 group (p < 0.05), with a weak but statistically significant positive correlation between CMT and disease severity (r = 0.245, p < 0.05), suggesting potential post-inflammatory retinal responses. No significant differences were observed in retinal nerve fiber layer (RNFL) or ganglion cell complex (GCL + IPL) thickness. However, mild negative trends in inferior RNFL and average GCL+IPL thickness may indicate early neurodegenerative changes. Notably, patients with comorbidities exhibited a significant reduction in superior and inferior RNFL thickness, pointing to possible long-term neurovascular impairment. These findings underscore the value of OCT imaging in identifying subclinical retinal alterations following COVID-19 and highlight the need for continued surveillance in recovered patients, particularly those with pre-existing systemic conditions.